EVALUATION OF THEORETICAL AND EMPIRICAL RESEARCHES ON TRANSFER PRICING - Novikovas, Martynas (Ekonomika, 2011)
This article is structured as follows. The introduction provides a brief explanation of transfer pricing and its significance to practitioners and researchers. The purpose of transfer pricing is next considered. Then the conception and assignment of transfer pricing are discussed. This leads to a review of major theoretical and empirical researches on transfer pricing. The paper finally calls for further researches which should preferably be grounded on field work within a theoretical framework.